Meningkatkan Pendidikan Bahasa Arab di Wilayah Pemerintah Daerah Ilorin Barat, Negara Bagian Kwara, Nigeria - Katibi, Saheed Ibrahim; Jamiu, Abubakar Sanusi (Program Pascasarjana UNU Surakarta, 2024)
Arabic historically served as Nigeria’s primary language for literacy, official documentation, and trade, notably within the Ilorin West Local Government Area of Kwara State. This study evaluates the role of the Arabic language in sustaining local Arabic education and examines the quality of teachers, curriculum, teaching methods, materials, and the learning environment. Despite its academic significance, Arabic is often mistakenly viewed as solely religious, hindering its educational progress. Utilizing a quantitative approach, the study gathered data through a questionnaire distributed among teachers and students across 10 purposively selected schools. The findings indicate that most respondents approve of the current curriculum and the integration of ICT, noting more effective modern methodologies in private schools. However, discrepancies exist between the learning environments of public and private schools. Findings reveal that 70% of respondents believe the current Arabic curriculum is suitable, while 80% agree that ICT integration has greatly contributed to effective teaching and learning. Also, 72% of respondents indicate that private schools employ modern and appropriate methodologies more effectively than public schools. The study also highlights that 70% of respondents find the teaching environments conducive, although there are significant differences between public and private institutions. The study concludes that private institutions are crucial in promoting Arabic education in Ilorin, though challenges like inadequate curricula and insufficient governmental support remain. Recommendations include curriculum re-evaluation, enhanced teaching resources, and better incentives to align Arabic education with national requirements, emphasizing its importance for Nigeria’s diverse developmental needs and advocating for strategic educational reforms.